Thinking about Feelings: The Study of Emotions in the New Testament Writings - Nils Neumann (Religions, 2024)
Growing attention has been directed towards affects and emotions in the New Testament texts within recent scholarship over the course of the past two decades. Although biblical exegesis of the 20th century suspected psychological interpretations of New Testament texts of being highly subjective and hence frail, recent research has developed a number of approaches that allow for addressing the subject in a methodologically controlled way. The aim of the present article is to review important monographs from the field of New Testament emotion research with special attention to their particular focuses and research methods. Despite some degree of overlap between these perspectives, six major areas of scholarly work can be identified: (1) “text psychology” that explains New Testament findings against the backdrop of modern psychological theories; (2) historical psychology that explores ancient notions of the affects; (3) narratology that observes recurring a narrative pattern in ancient descriptions of the affects; (4) rhetorical criticism that traces the rhetorical presentation of affects as well as the capability of rhetorical language to evoke affects in the addressees; (5) philosophy of the body that examines the bodily aspects of psychological dynamics; and finally (6) social history that identifies social functions of collective affects, e.g., in the formation and stabilization of social groups. After introducing each of these approaches briefly, the affect of desire (gr. ἐπιθυμία) will serve as a test case to demonstrate the possibilities and usefulness that the different perspectives offer. This way, it becomes clear that affects are by no means a by-product of theological teaching in the New Testament, but in fact indicators of true relevance.